PENGARUH MINAT BACA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VI MI MUHAMMADIYAH 11 BARA BARAYA - hasriani; Kose`, Eva; Dahlia; Nasir, A.Muhajir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to determine the influence of reading interest on the reading comprehension ability of sixth-grade students at MI Muhammadiyah 11 Bara baraya. This research employed a quantitative approach with an ex post facto design. The sample consisted of 22 students selected from the entire sixth-grade population. Reading interest data were collected using a questionnaire consisting of 10 Likert-scale statements, while reading comprehension ability was measured through an objective test comprising five items. Data analysis included descriptive statistics, the Shapiro–Wilk normality test, a linearity test using residual scatterplots, and simple linear regression analysis. The normality test showed that both variables were normally distributed (p > 0.05), allowing regression analysis to be conducted. The linearity test indicated that the relationship between the two variables was linear. Regression analysis revealed a significance value of 0.002 (< 0.05) and produced the regression equation Y=6.182+0.540X, indicating that reading interest has a positive and significant effect on reading comprehension ability. The coefficient of determination (R² = 0.374) shows that 37.4% of students’ reading comprehension ability can be explained by reading interest. Thus, this study concludes that increasing reading interest contributes significantly to the improvement of sixth-grade students’ reading comprehension ability.